« Qu’es chabat ». Une expérience de la disparition entre présence et rémanence. Situation de l’occitan dans le nord limousin - Jean-Pierre Cavaillé (Lengas)
In this paper, we attempt to analyze the situation of Limousin Occitan, or rather what remains of it, through a series of cases encountered during a campaign of documentary filmmaking in Occitan. In this analysis, a concept has emerged, that of “remanence”, in order to describe the situation of a language considered by the very people who speak it as dead, moribund or in a state of survival. The speakers are still numerous, but, especially if they belong to the latest generation who inherited it, they almost never find any more opportunities to speak it. Their capacity to communicate is often intact, but opportunities to exploit it are more and more scarce, within a context of almost absolute social and political indifference, and henceforth the renouncement of any form of transmission.